An Industrial systems design study on APO Pipes Industries Corporation (APIC) - Diaz, Irma R.; Fulgencio, Charisma B.; JUmaquio, Jayson S.; Lim, Fritz Ivan B. (Diliman, Quezon City College of Engineering, 2001)
An Industrial Systems Design study is made on APO PIPES INDUSTRIES CORPORATION (APIC). The said firm is engaged in the production and sale of Electric Resistance Welded (ERW) Black and Galvanized Iron Pipes for water lines, furniture, tubes, electric conduits, fences, structural members and parts of various fabricated equipment, deep well casings, and electric poles from ½ inch up to 4 inches in diameter. The study highlights the fundamental concepts and applications, including best practices, of Supply Chain Management. This particular discipline enables a business enterprise to allocate effectively its scare resources and increase system productivity through the alignment of its internal functions with its suppliers and customers. The study identifies the major functions/departments of the firm, namely: purchasing, inventory management, stores/warehouse management, manufacturing, customer service and transport operations. The current system of operations for each and every department is documented. This is especially important in evaluating the impact of the suggested changes or improvements in the system. Streamline Diagnostic Chart is one basic tool used in problem identification and analysis. Several criteria, upon due consideration of the outcome of such tool, are taken into consideration in deciding which problems to focus on. Based on critical problems, alternative recommendations are generated, evaluated and eventually implemented. Two major problems are identified, namely: (1) high cost of production, and (2) delay in the update of the stock level. Recommendations to address such issues are provided for. In Purchasing, conduct a supplier accreditation program and set the number of suppliers to a minimum per item and implement Local Area Network (LAN). In Inventory/Warehousing, conduct inventory check and update inventory records daily. In Production Planning, adopt a "single-crew" production schedule instead of a "double-crew" production schedule where there is separate crew for ERW and Galvanizing operations of the pipe production. Supply Chain Management is indeed very important in guiding a firm through the fulfillment of its goals and visions. Some recommendations which SCM calls for are simple to implement, yet not too costly, however the impact to the company is tremendous. In some cases, although some steps to be taken for improvement may be drastic and costly, Supply Chain Management looks ahead into the future as it considers the long-term benefits the firm shall reap.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 155 : Industrial Systems Design
Keywords: APO PIPES INDUSTRIES CORPORATION (APIC); Marketing channels--Management.; Delivery of goods--Management.; Physical distribution of goods--Management.; Customer services--Management.; Industrial procurement; Materials management; System design